Integrating Fuzzy Multi-Criteria Decision-Making and GIS for Sustainable Landfill Site Selection in Rapidly Urbanizing Ilorin City, Kwara State, Nigeria - Olatunde, G.; Babalola, A.; Ipadeola, O. A.; Olatunde, T. D. (Journal of Spatial Information Sciences, 2025)
An effective landfill site is essential for sustainable solid waste management, particularly in urban areas experiencing rapid population growth. This study develops a decision support framework for landfill site selection by applying Fuzzy Analytical Hierarchy Process (Fuzzy AHP) and weighted overlay techniques to evaluate potential landfill locations based on various factors. The study area covered Ilorin and its environs in Kwara State, Nigeria. The Fuzzy AHP was applied to determine the weights of relevant criteria, accounting for uncertainty in expert judgment. The weighted overlay technique was then used to integrate the various input criteria maps according to their assigned weights, thereby producing a landfill suitability map for the entire study area. The results of the findings show that 5% and 4% of the study area are unsuitable and less suitable, respectively, while 28% are moderately suitable, and 51% are suitable. On the other hand, 13% of the study area is highly ideal for landfill siting. The output suitability map was validated with two dumpsites. The old and decommissioned dumpsite at Ita Amo, which falls entirely within an unsuitable area, and the currently used site at Ago Aiyekale span both moderately suitable and suitable areas.
Keywords: Waste management; Landfill; Multi-criteria decision making (MCDM); Fuzzy Analytical Hierarchy Process (FAHP); Geographic Information Systems (GIS)